Ion mobility spectrometry-mass spectrometry (IMS-MS) for on- and offline analysis of atmospheric gas and aerosol species - Krechmer, Jordan E. (2020)
Measurement techniques that provide molecular-level information are needed to elucidate the multiphase processes that produce secondary organic aerosol (SOA) species in the atmosphere. Here we demonstrate the application of ion mobility spectrometry-mass spectrometry (IMS-MS) to the simultaneous characterization of the elemental composition and molecular structures of organic species in the gas and particulate phases. Molecular ions of gas-phase organic species are measured online with IMS-MS after ionization with a custom-built nitrate chemical ionization (CI) source. This CI-IMS-MS technique is used to obtain time-resolved measurements (5min) of highly oxidized organic molecules during the 2013 Southern Oxidant and Aerosol Study (SOAS) ambient field campaign in the forested SE US. The ambient IMS-MS signals are consistent with laboratory IMS-MS spectra obtained from single-component carboxylic acids and multicomponent mixtures of isoprene and monoterpene oxidation products. Mass-mobility correlations in the 2-D IMS-MS space provide a means of identifying ions with similar molecular structures within complex mass spectra and are used to separate and identify monoterpene oxidation products in the ambient data that are produced from different chemical pathways. Water-soluble organic carbon (WSOC) constituents of fine aerosol particles that are not resolvable with standard analytical separation methods, such as liquid chromatography (LC), are shown to be separable with IMS-MS coupled to an electrospray ionization (ESI) source. The capability to use ion mobility to differentiate between isomers is demonstrated for organosulfates derived from the reactive uptake of isomers of isoprene epoxydiols (IEPOX) onto wet acidic sulfate aerosol. Controlled fragmentation of precursor ions by collisionally induced dissociation (CID) in the transfer region between the IMS and the MS is used to validate MS peak assignments, elucidate structures of oligomers, and confirm the presence of the organosulfate functional group.